“The Absence of Student-Teacher Emotional Closeness", Rural and Urban English Teachers’ Voices during Covid-19 Pandemic - Moh. Taufik; Muhammad Burhanuddin Effendy (Journal of English Language Teaching and Linguistics, 2022)
The Corona Virus 19 (COVID-19) outbreak has made learning and teaching shifted to online. Some distinct modifications on teaching and learning need to be conducted, especially between those teaching English in rural and urban areas. This study is objected to eliciting teachers’ attitudes towards online learning of those teaching in rural and urban areas in the EFL context. A survey research design was employed to reach the objective with semi-interview and online questionnaires to collect data, distributed to the research subjects of 44 English teachers of secondary schools in rural and urban areas. The questionnaire was analyzed by finding the mean score of each item to determine tendencies, while the interview was analyzed by grouping the ideas into meaningful categories and was narratively described. The results showed significant differences in teachers' perception of teaching online in rural and urban areas, such as motivation, classroom management, technical support, and school and parents' support. It is then suggested that teaching online in rural and urban areas needs to be treated differently, a consideration for English teachers and the Ministry of Education to keep having ideal online learning and teaching.